Information Hiding Based on Audio Steganography using Least Significant Bit - Susilawati Mohamad, Fatma; Sahira Mohd Yasin, Nurul (International Journal of Engineering and Technology, 2018)
Steganography is the idea of hiding private or sensitive data or information within something that appears to be nothing out of the normal. A few problems arise especially in securing data and information when the information had been lost or stolen from unauthorized user. Traditionally, we give information manually using paper; it is possible that the information could be stolen by unauthorized user. The main objective of this study is to hide secret information in audio, so that other persons will not notice the presence of the information. The proposed method of this study is by using Least Significant Bit (LSB) algorithm to design an audio steganography. In the proposed method, each audio sample is converted into bits and then the text data is embedded. The expected result of this study will produce a steganography audio that will be able to hide data or information efficiently from unauthorized user, also to ensure the safety of the information in an authorized hand.Â Â